Evidence of Cross-boundary Use and Reuse of Digital Educational Resources - Vuorikari, Riina; Koper, Rob (International Journal of Emerging Technologies in Learning (iJET), 2009)
In this study an investigation using log-files of teachersâ?? Collections of educational resources in two different platforms was conducted. The goal was to find empirical evidence from the field that teachers use and reuse learning resources that are in a language other than their mother tongue and originate from different countries than they do, for this, the term cross-boundary use of learning resources is used. In both contexts behavioural evidence was found that cross-boundary use and reuse takes place, and it was shown that it correlates with the general use and reuse trends. Moreover, it was found that cross-boundary reuse, when compared to 20% of general reuse, was notably less (37% to 55% of it). The motivation to study cross-boundary use and reuse is to set a baseline for future studies, and to understand how it can be supported and enhanced in the future.